Mapping diaspora : African American roots tourism in Brazil - Pinho, Patricia de Santana (University of North Carolina Press, 2018)
"Brazil, like several countries in Africa, has become a major destination for African American tourists seeking the cultural roots of the black Atlantic diaspora. Drawing on over a decade of ethnographic research as well as textual, visual, and archival sources, Patricia de Santana Pinho investigates African American roots tourism, a complex, poignant kind of travel that provides profound personal and collective meaning for those searching for black identity and heritage. It also provides, as Pinho's interviews with Brazilian tour guides, state officials, and Afro-Brazilian activists reveal, economic and political rewards that support a structured industry"--